SILVOLIVE, a Germplasm Collection of Wild Subspecies With High Genetic Variability as a Source of Rootstocks and Resistance Genes for Olive Breeding - Díaz-Rueda, Pablo; Franco-Navarro, Juan D.; Messora, Rita; Espartero, Joaquín; Rivero-Núñez, Carlos M.; Aleza, Pablo; Capote, Nieves; Cantos, Manuel; García-Fernández, Jose L.; de Cires, Alfonso; Belaj, Angjelina; León, Lorenzo; et al. (Frontiers in Plant Science, 2020)
Wild subspecies of Olea europaea constitute a source of genetic variability with huge potential for olive breeding to face global changes in Mediterranean-climate regions. We intend to identify wild olive genotypes with optimal adaptability to different environmental conditions to serve as a source of rootstocks and resistance genes for olive breeding. The SILVOLIVE collection includes 146 wild genotypes representative of the six O. europaea subspecies and early-generations hybrids. These genotypes came either from olive germplasm collections or from direct prospection in Spain, continental Africa and the Macaronesian archipelago. The collection was genotyped with plastid and nuclear markers, confirming the origin of the genotypes and their high genetic variability. Morphological and architectural parameters were quantified in 103 genotypes allowing the identification of three major groups of correlative traits including vigour, branching habits and the belowground-to-aboveground ratio. The occurrence of strong phenotypic variability in these traits within the germplasm collection has been shown. Furthermore, olive wild relatives are of great significance to be used as rootstocks for olive cultivation. Thus, as a proof of concept, different wild genotypes used as rootstocks were shown to regulate vigour parameters of the grafted cultivar 'Picual' scion, which could improve the productivity of high-density hedgerow orchards.